Fundamental housing prices in the Baltic States: empirical approach - Darius Kulikauskas (Baltic Journal of Economics, 2016)
This paper investigates if the imbalances in the Baltic residential real estate markets that were mounting up prior the crisis of 2008–2009 could have been detected in real time. It develops an empirical framework comprised of various empirical techniques for assessing housing price misalignments from their fundamental prices. For this purpose, several statistical indicators (price-to-rent ratio, price-to-income ratio, price deviations from Hodrick-Prescott filtered trend) together with the estimates from equilibrium equations are computed. The use of those indicators in a consistent graphical framework reduce the uncertainty associated with using only a single metric and allows to arrive to clearer conclusions about residential real estate price misalignments. It is shown that the framework would have been able to identify the overvaluation in the residential real estate markets in the Baltics as early as in 2005.
Keywords: R3; R30; R31; 330; Housing; real estate; prices; fundamentals; panel; Lithuania; Latvia; Estonia